2017
DOI: 10.1104/pp.17.00493
|View full text |Cite
|
Sign up to set email alerts
|

An Animal-Like Cryptochrome Controls the Chlamydomonas Sexual Cycle

Abstract: Cryptochromes are known as flavin-binding blue light receptors in bacteria, fungi, plants, and insects. The animal-like cryptochrome (aCRY) of the green alga has extended our view on cryptochromes, because it responds also to other wavelengths of the visible spectrum, including red light. Here, we have investigated if aCRY is involved in the regulation of the sexual life cycle of, which is controlled by blue and red light at the steps of gametogenesis along with its restoration and germination. We show that aC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 64 publications
(150 reference statements)
2
39
0
Order By: Relevance
“…29 We found that this recombination is in competition with protonation of FAD •to form the neutral, red light-absorbing radical FADH • that is the primary target for CraCRY-based red light responses of Chlamydomonas cells. 21,22,104 The protonation was accelerated and hence more efficient at lower pH (see Figure S2D and SI, Section S2.2 for more details), explaining a previous observation 23 Remarkably, on a time scale up to a few nanoseconds, there are less losses by recombination in in the Y373F mutant protein (~20%) than in WT (~40%; Figures 3A and 3C). This may indicate that the .…”
Section: ~60%supporting
confidence: 69%
See 1 more Smart Citation
“…29 We found that this recombination is in competition with protonation of FAD •to form the neutral, red light-absorbing radical FADH • that is the primary target for CraCRY-based red light responses of Chlamydomonas cells. 21,22,104 The protonation was accelerated and hence more efficient at lower pH (see Figure S2D and SI, Section S2.2 for more details), explaining a previous observation 23 Remarkably, on a time scale up to a few nanoseconds, there are less losses by recombination in in the Y373F mutant protein (~20%) than in WT (~40%; Figures 3A and 3C). This may indicate that the .…”
Section: ~60%supporting
confidence: 69%
“…In contrast to other cryptochromes, CraCRY appears to be capable of inducing a genetic response not only to blue, but also to red light. [20][21][22] This feature is probably related to another unique property of CraCRY, the very efficient formation and stabilization of its semireduced (red light-absorbing) flavin cofactor (FADH • ) that can be easily accumulated under blue light illumination and lives for seconds to minutes (depending on pH). 20,23 This process relies on the oxidation of the phenolic moiety of the tyrosine residue Y 373 as its mutation to phenylalanine abolishes this effect.…”
Section: Introductionmentioning
confidence: 99%
“…The isolation and manipulation of zygotes are facilitated by plating mating mixtures on 4% agar plates, as zygotes adhere strongly to the surface of this medium. Zygotes are later induced to germinate (undergo meiosis) via transfer onto rich medium in the light, which is perceived by the blue light photoreceptors cryptochrome and phototropin (Huang and Beck, 2003;Müller et al, 2017;Zou et al, 2017). Chlamydomonas can be used for tetrad analysis via the dissection of the four germinated meiotic products, as they carry one or the other mating type, which segregate in a 2:2 ratio.…”
Section: Reproductive Cyclementioning
confidence: 99%
“…Among the genes associated with light sensing in Chlamydomonas, cryptochromes and phototropin appear to be obvious candidates to play roles in blue-light-dependent regulatory mechanisms (Huang et al, 2002;Zorin et al, 2009;Ahmad, 2016;Petroutsos et al, 2016;Duanmu et al, 2017Zou et al, 2017). Among the five genes encoding cryptochrome (CRY) photoreceptors (for a recent review on algal CRYs, see Duanmu et al, 2017;Kottke et al, 2017), expression levels for the gene encoding plant CRY (pCRY) are highest, peak in the dark, and are rapidly repressed upon the onset of light.…”
Section: Hmox1 Is Dispensable For Light-dependent Transcript Accumulamentioning
confidence: 99%